1997
DOI: 10.1590/s0037-86821997000100004
|View full text |Cite
|
Sign up to set email alerts
|

Human parvovirus B19 infections among exanthematic diseases notified as measles

Abstract: A total of 1397 sera collected from 1095 cases of exanthematic disease notified as measles in ES and RJ states during July 1992 to December 1994 were investigated. These sera were first tested for measles and rubella specific IgM. When they proved negative, they were tested for B19 specific IgM by an enzyme immunoassay. B19 infection was confirmed in 27 (2.5%) of these cases. Sera from 194 negative cases for measles and rubella IgM received from other Brazilian states were also investigated and B19 infection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 19 publications
(10 reference statements)
2
21
0
2
Order By: Relevance
“…Outbreaks of parvovirus B19 infection in temperate climates are more common in late winter and spring months, though cases may be recorded in any month (Cohen 1995). In our study, 92.4% of the cases were recorded during this season, similar to the report by Cubel et al (1997) for other regions of Brazil. However, different findings were reported in the Amazon region by Miranda et al (1989), who described higher incidence of the disease during the first half of the year, a season of heavy rainfall and high humidity in the North of our country.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Outbreaks of parvovirus B19 infection in temperate climates are more common in late winter and spring months, though cases may be recorded in any month (Cohen 1995). In our study, 92.4% of the cases were recorded during this season, similar to the report by Cubel et al (1997) for other regions of Brazil. However, different findings were reported in the Amazon region by Miranda et al (1989), who described higher incidence of the disease during the first half of the year, a season of heavy rainfall and high humidity in the North of our country.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, parvovirus B19 infection shares the seasonal pattern with rubella and measles, i.e., late winter and spring, which makes clinical diagnosis even more difficult. In Brazil, because of the reduction in measles and rubella incidence rates after the introduction of national mass vaccination campaigns, parvovirus B19 infection has increased its relative importance in the surveillance of rash diseases (Cubel et al 1997, Ministério da Saúde 1999, Oliveira et al 2001a). However, without the aid of laboratory methods, the public health relevance is likely to be unnoticed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that false-positive measles IgM results can occur, particularly with parvovirus B19 and rubella virus, which have similar clinical presentations (3,6,8). In addition, it has been shown that reactivation of IgM responses to multiple viruses (including measles and rubella viruses and parvovirus B19) can occur in response to infection by one of the viruses (14).…”
mentioning
confidence: 99%
“…Compared to EIA (Cubel et al 1997) the sensitivity of IFA with VP1 was 100% and with VP2, 98.7%; the specificity with VP1 was 86.6% and with VP2, 93.3%. The 2 sera IgG negative by EIA and positive by VP1 IFA, were confirmed as B19 IgG positive by a sensitive and specific anti-VP1 Western-blotting assay (Pinheiro et al 1997), so the anti-VP1 IgG IFA could be considered 100% sensitive and specific.…”
Section: Discussionmentioning
confidence: 87%
“…The sera had previously been tested for anti-B19 IgM by MACEIA using the native virus as antigen (Cubel et al 1994) and for anti-B19 IgG using baculovirus recombinant capsids (Kajigaya et al1991) containing VP2 (70%) and VP1 (30%) in a indirect enzyme immunoassay (EIA) (Cubel et al 1997). All sera were now tested for anti-B19 IgM and IgG using Sf9 cells expressing both VP1 and VP2 by immunofluorescence assay (IFA) as described bellow.…”
Section: Methodsmentioning
confidence: 99%